PENGARUH BRAND FAMILIARITY TERHADAP PURCHASE INTENTION MELALUI BRAND FIT PADA HOTEL MULIA JAKARTA - Widiawaty Widiawaty (Jurnal Manajemen dan Pemasaran Jasa, 2015)
The purpose this paper is to examine the effects of Brand familiarity and Brand Fit on Purchase Intention towards the offerings of co branded hotels. The findings showed that the fit between cobrands mediate the relationship between Brand familiarity and Purchase Intention. In particular, a well-known co-branded hotel a high level of Brand Fit could directly or indirectly affect consumer decision-making processes regarding Purchase Intention towards the co-brand. conversely, a lessfamiliar co-branded hotel had positive effect on Purchase Intention only if respondents perceived a good fit between allied brands. Brand Fit could be a more important factor than Brand familiarity in influencing the success of hotel co-branding strategis. future research to examinate the co-branding concept in different social and cultural contexts and also from different perspectives, such as owners or manager is recommended. Most hospitality studies focus on co-branding between hotels and restaurant. This study empirically investigated the effects co-branding on consumer behavior in thehotel sector.